Unggah Mandiri Local Content: Tren Layanan Perpustakaan Perguruan Tinggi - Ana Pujiastuti (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
Student university’s final report (thesis and dissertation) abundant in the library. The abundance of these resources requires librarians make a breakthrough easy to information retrieval. This collection is limited access, one user and unique. Will be the maximum in utilization if librarians do innovation. Forms final report begins with hardcover binding form to the CD collection. Collaboration technology in library information into the background of self-contained systems upload final report. Upload independent chains will shorten the handover-upload the final report in the library. There are three components in the success of independent upload final report, namely Standard Operating Procedure (SOP) clear, professional competence of librarians and IT support. These three components are inseparable and intertwined in the process of self-upload success. Expectations with self-contained systems upload final report is easy retrieval of information so that more resources maximized.